Unveiling unstable non-acid incidence in holstein cows fed with corn silage or sugarcane - Rocha, Lethiane Garcia (2021)
We aimed to evaluate the incidence of unstable non-acid milk (UNAM) in cows fed either sugarcane or corn silage. Secondly, we aimed to evaluate the effect of temperature, daily variation and alcohol grades (72º, 78º and 80º) on UNAM incidence. The experiment was conducted as split-plot cross-over design with two periods and two roughage types (sugarcane or corn silage). Thirteen multiparous Holstein cows with an average of 281 days in milk were randomly distributed into two diets. Individual blood (analysis of total proteins, albumin, urea, calcium, phosphorus, magnesium, iron, chloride, glucose and lactate) and milk samples (analysis of protein, fat, lactose and total solids, somatic cell count, profile protein electrophoretic) were collected during the last 4 days of each period. Alcohol test and dornic acidity were conducted in milk samples at 36ºC and 4ºC. Analyzes of zeta potential, micelle size and macrominerals in the casein micelle (calcium, phosphorus, magnesium and potassium) were also determined in refrigerated milk samples. The use of sugarcane, the degree of alcohol and the temperature of the milk at the time of the analysis affected the incidence of UNAM. The zeta potential, αS2-casein, blood ionic calcium, lactate and glucose were positively correlated with UNAM while lactose, phosphorus and potassium were negatively correlated with UNAM. Sugarcane-fed cows had increased levels of ionic calcium and glucose in the plasma, and reduced the levels of magnesium and urea, also significantly altered the protein profile of milk with lower levels of bovine serum albumin (BSA), β-casein and α-lactalbumin and greater αS1-casein content, all of which were correlated with the incidence of UNAM. Nevertheless, we found no roughage type effect on the variables mostly associated with UNAM, which are: changes in salts in the casein micelle, and consequently the zeta potential, and the k-casein fraction. This study brought important discoveries to unveil why cows manifest UNAM, however it also evidenced the need of further studies to better understand the physiological mechanisms that directly affect the stability of milk protein. Keywords: Electrophoretic profile. Casein micelle. Zeta potential